What the web will bring next [ICTs for agriculture] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2009)
Internet technology is evolving rapidly. ICT Update reported on projects using web 2.0 applications in 2007, but the next generation of web services is already available.